Pandangan Masyarakat Terhadap Tradisi Larangan Pernikahan Antara Orang Sunda Dengan Jawa - Andriyana, Muhamad Fikri; Masrokhin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The aim of this scientific work is to examine the perspective of Islamic law and society regarding the tradition of prohibiting marriage between Sundanese and Javanese people based on the belief that the prohibition emerged. People's views on the problems faced by Sundanese and Javanese couples, as well as